Manajemen Sarana Prasarana Berbasis Teknologi untuk Pembelajaran Abad 21 - Salsabiiliana Putri Sajdah; Putri Juwita; Abdiel Muhammad Arkananta; Hesti Kusumaningrum (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
In the 21st century, the rapid development of technology requires changes in education management, especially in the management of facilities and infrastructure. Technology-based management not only meets the physical needs of schools but also creates an innovative learning environment that adapts to current developments This research discusses effective strategies and approaches when planning, implementing and evaluating the use of technology in educationm Overall, this research aims to contribute to the development of technology-based education management to create a higher quality learning environment that meets the needs of the 21st century.